(3GdSfI Chdi (BLMDs - (3RcQjGA(B, (3LeYIs ((3GdLRGFQ (B:s (3OGQ gheI ddWHGYI hGdfTQ hGdJhRjY(B,s, 2018)
(3gPG GdcJGH YHGQI Yf eLehYI ef GdJeGQjf hGdCYeGd GdehLgI aj eGOI GdEMUGA (BI (3GdNGUI HWdGH GdSfI GdChdi LPY eTJQc ejOGf GdYdhe GdGbJUGOjI, GdJLGQjI hYdhe GdJSjjQ HUaI NGUI hcd GdWdHI GdOGQSjf dgPg GdeGOI hGdegJejf HGdGMUGA HUaI YGeI(B. (3HGdGVGaI Gdi hVY GdMd GdJaUjdj dcd JeQjf ef JeGQSjf GdcJGH hefGbTJgG HCSdhH Ydej hGVM hYHGQI HSjWI heagheI , abO Je EQaGb cd aUd ef aUhdg HedNU jJVef JPcjQG HGdOQS hCge eG jMJGLg GdWGdH aj GdMd, eeG jSGYOg Ydi GdeQGLYI GdSQjYI hGSJMVGQ GdeYdheI aj MjfgG (B. (3hYdjg aEffG fYJbO Gf gPG GdcJGH jYO COGI MbjbjI aj GdeSGYOI Ydi GdEdeGe HeHGOF GdEMUGA GdhUaj hGdJMVjQ GdLjO deNJda GdEeJMGfGJ GdJj JNU gPg GdeGOI(B.s
(3GdeQGLY U(B.213s
Keywords: (3GdEMUGAs